2009
DOI: 10.1186/1471-2458-9-41
|View full text |Cite
|
Sign up to set email alerts
|

Are youth mentoring programs good value-for-money? An evaluation of the Big Brothers Big Sisters Melbourne Program

Abstract: Background: The Big Brothers Big Sisters (BBBS) program matches vulnerable young people with a trained, supervised adult volunteer as mentor. The young people are typically seriously disadvantaged, with multiple psychosocial problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 16 publications
0
21
0
2
Order By: Relevance
“…Consequently, research aimed at establishing a link between youth mentoring status and various outcomes must adjust for these factors. Studies have shown that the pace with which mentoring relationships develop is influenced by mentee demographics with boys and racial mi-nority youths waiting significantly longer to be mentored than other groups (Furano, Roaf, Styles, and Branch 1993;Moodie and Fisher 2009). Mentored girls have been found to experi-ence longer mentoring relationships than boys do (Rhodes, Lowe, Litchfield, and Walsh-Samp 2008).…”
Section: Correlates Of Youth Mentoring Statusmentioning
confidence: 99%
“…Consequently, research aimed at establishing a link between youth mentoring status and various outcomes must adjust for these factors. Studies have shown that the pace with which mentoring relationships develop is influenced by mentee demographics with boys and racial mi-nority youths waiting significantly longer to be mentored than other groups (Furano, Roaf, Styles, and Branch 1993;Moodie and Fisher 2009). Mentored girls have been found to experi-ence longer mentoring relationships than boys do (Rhodes, Lowe, Litchfield, and Walsh-Samp 2008).…”
Section: Correlates Of Youth Mentoring Statusmentioning
confidence: 99%
“…Deployed to promote engagement with schooling (Pryce 2012), or informal learning or employment (Sandford, Armour and Stanton 2010), it is often specifically targeted at those young people experiencing social disadvantage or deemed 'at risk' (Moodie and Fisher 2009 Jupp (2013) has called the 'thickening' of social 4 policy interventions targeting particular population groups. As these multi-agency strategies are mobilised to develop forms of governance around the behaviours of young people, particularly those seen to be 'difficult to reach' and 'at risk', the immediate practices of mentoring are thus situated within wider circuits of social policy.…”
Section: Youth Mentoring and Social Policy: Attending To The Relationalmentioning
confidence: 99%
“…Youth mentoring programs for disadvantaged children are increasingly advocated as a means of redressing the decreased availability of parent or family support and guidance in the lives of youth (Moodie & Fisher, 2009; Rhodes, 2002; Spencer, 2006). Mentoring is a dyadic psychosocial intervention wherein a more experienced or knowledgeable individual is brought into a close relationship with a less knowledgeable person in order to provide support and guidance (Karcher, Nakkula, & Harris, 2005; Rhodes, 1994).…”
mentioning
confidence: 99%